2007
DOI: 10.1002/rcm.3313
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature ultra‐performance liquid chromatography coupled to hybrid quadrupole time‐of‐flight mass spectrometry applied to ibuprofen metabolites in human urine

Abstract: The application of sub-2 microm porous particle liquid chromatography (LC) operated at elevated temperatures, coupled with time-of-flight mass spectrometry (MS), to the separation and identification of metabolites of ibuprofen present in human urine following oral administrations is illustrated. The LC/MS system generated a high-resolution analytical separation that, with an analysis time of 20 min, provided a peak capacity in the order of ca. 350. Using this system a total of nine glucuronides of the drug and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Analytical conditions including the column [12], temperature [13], rapid gradients [14] have been tested, as well as the influence of sample separation techniques [15] and sample storage time [9] on urinary metabolite profiles. In the present study, we have compared various LC conditions and sample pre-treatments in order to further optimise the methodology for untargeted metabolite profiling.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical conditions including the column [12], temperature [13], rapid gradients [14] have been tested, as well as the influence of sample separation techniques [15] and sample storage time [9] on urinary metabolite profiles. In the present study, we have compared various LC conditions and sample pre-treatments in order to further optimise the methodology for untargeted metabolite profiling.…”
Section: Resultsmentioning
confidence: 99%
“…Fenselau and Johnson (1980) and Niemeijer et al (1991) reported that the O bond to the aromatic ring is not readily broken in the mass spectrometric analysis of phenols or phenol derivatives. The m/z 193 ion is considered to be the deprotonated glucuronic acid ion produced by cleaving the carboxyl group C-O bond, as reported by Jaggi et al (2002) and Plumb et al (2007) on the acyl O-glucuronides of desmethylnaproxen and ibuprofen. Given the mass spectrometric analysis and the fact that G2 is alkali-labile, this strongly suggests that G2 is the acyl O-glucuronide of T-5224.…”
Section: Discussionmentioning
confidence: 99%
“…An additional benefit of using a harder, nonselective fragmentation followed by a fullscan data acquisition or data-dependent acquisition in LC-HRMS is the fact that the acquired data can be evaluated even retrospectively on unexpected metabolites/analytes. Fragmentrich spectra suitable for data interpretation were also described by Plumb et al [34] using alternating high-low collision energies produced in the collision cell of a Q-TOF instrument.…”
Section: Ionization and Fragmentation Techniquesmentioning
confidence: 99%